Effect of seed layer on the growth of zinc oxide nanowires by chemical bath deposition method - Azmi, Zaidatul Hanis; Mohd Aris, Siti Nurnadiah; Abubakar, Shamsu; Sagadevan, Suresh; Siburian, Rikson; Paiman, Suriati (MDPI, 2022)
This study concentrated on the effect of the ZnO seed layer on the growth of ZnO nanowires by the chemical bath deposition method. Multilayer coatings were used to control the thickness of the seed layer of one layer, three layers, and five layers. The seed layer thickness was measured using a profilometer at 14.43, 33.31, and 53.13 nm for one-layer, three-layer, and five-layer samples, respectively. The samples were then immersed in a chemical bath deposition solution at 90 °C for 3 h to allow ZnO nanowires to grow. The X-ray diffraction (XRD) pattern of seed layers revealed a polycrystalline wurtzite structure with (101) orientation as the dominant peak in all samples. Field emission scanning electron microscopy (FESEM) revealed that ZnO nanowires grown in a single layer have a flower-like structure, whereas ZnO nanowires grown in three and five layers have a rod-like structure. Further, ImageJ software revealed that the diameter and length of the ZnO nanowires were in the 40–90 nm and 100–900 nm ranges, respectively. The five-layer sample had the highest density of ZnO nanowires at 668 µm−2, followed by the three-layer sample and the one-layer sample. However, the ZnO nanowires in the five-layer and one-layer samples are not vertically aligned. On the other hand, the three-layer sample had the best vertical alignment of this group of samples.